THE NEXUS BETWEEN ELECTORAL SYSTEMS AND DEMOCRATIC GOVERNANCE: EVIDENCE FROM INDONESIA - Khafid Ainul Yaqin, Muhammad; Miftakhul Laily, Yaen; Wayan Desi Budha Jayanti, Ni (International Journal of Multidisciplinary Reseach, 2025)
This study examines the relationship between electoral systems and democratic governance in Indonesia by analyzing the implementation of democratic principles in Indonesian elections. Using a literature review methodology, this research evaluates Indonesia's electoral system against four key elements of democratic elections: competitiveness, periodicity, inclusiveness, and definitiveness. The findings reveal that while Indonesia has established strong legal frameworks and institutional mechanisms for democratic elections, challenges remain in translating campaign intensity into meaningful voter engagement. The study demonstrates that Indonesia has successfully implemented periodic leadership transitions, maintains inclusive electoral processes through comprehensive legislation, and enables citizens to exercise informed electoral choices. However, low voter participation and limited impact of candidate programs on voter preferences indicate areas requiring improvement. This research contributes to understanding democratic governance in emerging democracies and provides practical recommendations for electoral system enhancement.